Kinetic and kinematic profile of eccentric quasi-isometric loading - Oranchuk, D. J.; Diewald, S. N.; McGrath, J. W.; Nelson, A. R.; Storey, A. G.; Cronin, J. B. (Sports Biomechanics, 2021)
Eccentric quasi-isometric (EQI) contractions (maintaining a yielding contraction for as long as possible, beyond task failure) have gained interest in research and applied settings. However, little is known regarding the biomechanical profile of EQIs. Fourteen well-trained males performed four maximal effort knee-extensor EQIs, separated by 180 seconds. Angular impulse, velocity, and time-under-tension through the 30-100º range of motion (ROM), and in eight ROM brackets were quantified. Statistical parametric mapping, analyses of variance, and standardised effects detected between-contraction joint-angle-specific differences in time-normalised and absolute variables. Mean velocity was 1.34º·/s with most (62.5 ± 4.9%) of the angular impulse imparted between 40-70º. Most between-contraction changes occurred between 30-50º (p= 0.067, ES = 0.53 ± 0.31, 60 ± 52%), while measures remained constant between 50-100º (= 0.069-0.83, ES = 0.10 ± 0.26, 14.3 ± 24.6%). EQIs are a time-efficient means to impart high cumulative mechanical tension, especially at short to medium muscle lengths. However, angular impulse distribution shifts towards medium to long muscle lengths with repeat contractions. Practitioners may utilise EQIs to emphasize the initial portion of the ROM, and limit ROM, or apply EQIs in a fatigued state to emphasize longer muscle lengths.